An examination of net-zero commitments by the world's largest banks: Promising beginnings, significant room for improvement - Carlo Di Maio; Maria Dimitropoulou; Zoe Lola Farkas; Sem Houben; Georgia Lialiouti; Katharina Plavec; Raphaël Poignet; Eline Elisabeth Maria Verhoeff (European Central Bank (ECB), 2023)
We examined the net-zero commitments made by Global Systemically Important Banks (G-SIBs). In recent years, large banks have significantly increased their ambition and now disclose more details regarding their net-zero targets. There is also growing convergence, with the vast majority of G-SIBs now being part of netzero alliances. Despite this progress, some practices should be further improved. We assessed climate-related risks disclosures publicly available for G-SIBs in 2022. The paper gives an overview about potentially problematic disclosure practices with regards to their net-zero commitments. It identifies and discusses a number of observations, such as the significant differences in sectoral targets used despite many banks sharing the same goal, the widespread use of caveats, the missing clarity regarding exposures to carbon-intensive sectors, the lack of clarity of "green financing" goals, and the reliance on carbon offsets by some institutions. The identified issues may impact banks' reputation and litigation risk and risk management. The paper explains how the introduction of comparable international rules on climate disclosure and the introduction of transition plans, as envisaged and partly already in place in the European Union, could help mitigate these risks.
Keywords: G2; G21; G28; Q5; Q54; 330; net-zero commitments; disclosures; climate scenarios; transition plans; greenwashing; litigation risk